FACTORS INFLUENCING ACCOUNTING STUDENTS' FINANCIAL LITERACY AT WIDYATAMA UNIVERSITY, BANDUNG - PA. Andiena Nindya Putri; Arlina Pratiwi Purba; Ahmad Sani (Jurnal Ekonomi, 2023)
The spread of the Covid 19 virus has shaken the economy in various countries, including Indonesia. This is due to the lack of financial literacy in society, starting from the young adult phase, especially for students. Financial problems can cause stress, and about 73% of students in the campus community report experiencing difficulties related to finances. The purpose of this study was to determine the extent to which factors influence financial literacy such as financial attitudes, family environment, peer pressure and financial efficacy . This type of research is quantitative research with a descriptive approach. The samples studied were all S1 Faculty of Economics Accounting Study Programs at Widyatama University Bandung, sampling in this study used purposive sampling, so using the above calculation it was known that the population was 251 students, a sample of 155 students was taken in this study. Data analysis techniques in this study used validity tests, reliability tests and structural model tests. The results of this study indicate that family environmental factors do not have a significant effect on financial literacy, while financial efficacy factors have a significant effect on financial literacy, financial attitudes have a significant effect on financial literacy, and peer pressure has a significant effect on financial literacy. This is consistent with research (Thomas & Subhashree, 2020) that financial knowledge, financial attitudes, parental influence, and peers have a direct and positive effect on the level of financial literacy in Engineering undergraduate students